2007
DOI: 10.1074/jbc.m611907200
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Down-regulates MHC II Expression in Microglia and Macrophages through Inhibition of IRF-1 and Protein Kinase C (PKC)α/βII

Abstract: Experimental allergic encephalomyelitis, an autoimmune disorder mediated by T cells, results in demyelination, inflammation, and axonal loss in the central nervous system (CNS). Microglia play a critical role in major histocompatibility complex class II (MHC II)-dependent antigen presentation and in reactivation of CNS-infiltrated encephalitogenic T cells. Minocycline, a tetracycline antibiotic, has profound anti-inflammatory properties and is experimentally used for treatment of many CNS disorders; however, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 27 publications
8
108
0
Order By: Relevance
“…IFN-g and TNF-a are the main inducers of IDO activation. 5,6 Minocycline has already been shown to block IFN-g-mediated protein kinase C (a/bII) phosphorylation and nuclear translocation of both protein kinase C (a/bII) and IRF-1, 17 which is necessary for IDO activation. It also inhibits nuclear factor k-B and MAP kinase activation, 35 which are both necessary for the synergistic effects of TNF-a and IFN-g on IDO activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IFN-g and TNF-a are the main inducers of IDO activation. 5,6 Minocycline has already been shown to block IFN-g-mediated protein kinase C (a/bII) phosphorylation and nuclear translocation of both protein kinase C (a/bII) and IRF-1, 17 which is necessary for IDO activation. It also inhibits nuclear factor k-B and MAP kinase activation, 35 which are both necessary for the synergistic effects of TNF-a and IFN-g on IDO activation.…”
Section: Discussionmentioning
confidence: 99%
“…Minocycline has potent anti-inflammatory effects independent from its microbicidal properties, as it is well-known to inhibit macrophage and microglial activation. Of all the tetracyclines, it has the greatest permeability through the blood-brain barrier, 17 and it confers therapeutic benefits in many CNS disease models, including ischemia, 18 Parkinson disease, 19 amyotrophic lateral sclerosis 20 and multiple sclerosis. 17 The tryptophan analog 1-methyltryptophan (1-MT) was chosen for the second approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also suggested that tetracyclines induce DC-like cell differentiation at sites of RANKL expression. In addition, tetracyclines were shown to suppress inflammation (46)(47)(48)(49). The development of a drug-delivery system for tetracyclines will facilitate their use in the suppression of bone loss induced by local inflammation, including rheumatoid arthritis and periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The study of CIITA modifications would benefit from similar strategies. Given the diverse range of genes regulated by CIITA, it is perceivable that dysregulated CIITA activity has been implicated in multiple pathophysiological processes, which include cancer (17,36), atherosclerosis (3,14), encephalitis (28), encephalomyelitis (20), carditis (5), and pulmonary fibrosis (Xu and Smith, unpublished). Because CIITA activity is modulated by the PTM machinery, it is now possible to target a host of PTM components in the development and/or optimization of therapeutic interventions against these pathologies.…”
Section: Perspectivesmentioning
confidence: 99%